DRC and TSC measurement, of hevea rubber latex by microwave techniques. - Khalid, Kaida; Mat Hassan, Yahya; Ramli, Abd Rahman (1989)
As an agricultural country and the world's largest producer of rubber, the determination of total solid content (TSC) and dry rubber content (DRC) of hevea rubber latex requires a special attention. Its significance covers aspects on quality and process controls. In this paper the development of the sensor utilized low microwave power (- 10mW) and microwave drying technique utilizing high microwave power (> 500W) for the above measurements will be discussed.The sensor, the waveguide reflected type, has been analysed and optimized for the highest precision. The experimental results showed that the reflected wave from the sample give a good relationship with the TSC and DRC of the latex.It also gives a better sensitiVity for a range of water content between 70% to 100% as compared with transmission technique. This technique is capable of reproducing duplicate result < 0.7% and an accuracy < 1% (unit TSC and DRC) as compared with the standard laboratory method. This method which is based on the measurement of water content in the latex is not much affected by many adulterants and temperature as compared with the hydrometric method. This kim of sensor is proposed for development of an accurate, rapid, ease of operation and portable instruments and suitable to be used at latex collecting centres. Furthermore it has a great potential to be used in the process control in the latex based imustries. The standard methods for the TSC and DRC determinations involve with the drying of a sample in conventional oven· at 700 C for two and twelve hours, respectively. These techniques, which are time consuming,can be replaced by the microwave drying technique offering faster drying rates and comparable accuracy.In the DRC determination, drying time of the coagulum sheet (with initial moisture content 20 - 40%) took less than 10 minutes and an average drying rate is about 0.16 gm/min. The average output of this method is > 60 determination/operator/day and the tappers can witness the whole operation of test on their latices and get the test results on the day of operation. The application of these microwave techniques hopefully will provide proper methods with acceptable precision in the TSC and DRC measurements.